Technical and Vocational Education and Training College Lecturers and 21st-Century Skills: Awareness and Implications for Teaching Practices - Pharamela, Solomon; Singh-Pillay, Asheena (Journal of Technical Education and Training, 2025)
The increasing demand for 21st-century skills in the workforce places new expectations on educators, including TVET lecturers, who play a critical role in preparing students for evolving industry needs. This study explored the awareness and understanding of 21st-century skills among TVET lecturers and examined how this awareness influences their teaching practices. A mixed-methods approach was employed, incorporating surveys, interviews, classroom observations, and document analysis. Results indicate that while lecturers are aware of critical skills such as communication, collaboration, creativity, and critical thinking, their practical application in teaching practices varies due to challenges such as curriculum rigidity, lack of resources, and insufficient professional development opportunities. The study concludes with strategic recommendations for professional development and curriculum adjustments necessary to foster 21st-century skills among lecturers.